E-056 Current applications of oct in neurointerventional angiography: a retrospective cross-sectional observational analysis. (22nd July 2019) - Luther, E; Starke, R
Abstract : Introduction: Optical coherence tomography (OCT) is a novel intraluminal imaging modality that uses optical backscattering to produce cross-sectional images of tissue. The technique has already proven useful in the coronary vasculature for evaluation of plaques, stent-vessel interactions, dissections and intimal healing. However, there is limited data regarding the current applications of OCT in cerebrovascular imaging. Methods: We performed a retrospective analysis of the Nationwide Inpatient Sample (NIS) between 2009–2015. Patients with an ICD-9-CM procedure code indicating use of OCT (38.25) and an ICD-9-CM diagnosis code indicating either presence of an intracranial aneurysm/SAH (437.3 or 430), carotid/vertebrobasilar/intracranial atherosclerosis with or without associated cerebral infarction (433.xx or 434.xx), or carotid/vertebrobasilar arterial dissection (443.21 or 443.24) were included. Primary diagnosis codes, primary procedure codes, hospital region, hospital teaching status, rate of iatrogenic neurologic injury, and time to use of OCT were evaluated in an effort to identify current inpatient OCT practices in neurointerventional angiography. Results: 7 patients in the NIS were identified as having undergone OCT for a cerebrovascular pathology between the years of 2009–2015. Average age was 71.3 years. 2 patients were female and only 28% were elective admissions. 4 patients were discharged home, 2 would be discharged to a long-term care facility and 1 patient would require home health care. The two most common primary diagnoses were carotid artery occlusion/stenosis with or without mention of cerebral infarction (433.11 and 433.10, respectively). The two most common primary procedures were diagnostic cerebral angiography and carotid endarterectomy (88.41 and 38.12, respectively). Median LOS was 3 days. The only hospital regions represented were the Northeast and the South and those in the South were solely performed at urban non-teaching hospitals while those in the Northeast were only at urban teaching hospitals. Interestingly, OCT was performed on the same day as all primary procedures except for one patient who underwent OCT two days prior to undergoing elective carotid endarterectomy. Interestingly, this was also the only patient who experienced iatrogenic cerebral infarction/hemorrhage during the admission. Conclusions: Although OCT has proven to be an effective adjunct imaging modality in the coronary vasculature, few neurointerventionalists have adopted it since it received FDA-approval in 2010. Moreover, it appears that those who have begun to use it have only applied it to atherosclerotic disease despite the fact that several animal and cadaveric studies have proven it effective in identifying both aneurysm neck morphology and endothelialization post-embolization. The utility and efficacy of OCT in various cerebrovascular pathologies warrant further investigations. Disclosures: E. Luther: None. R. Starke: None.